Perancangan dan Pengembangan Buku Cerita Ilustrasi tentang Kisah Nabi Muhammad Saw: “Keistimewaan Kucing” dengan Teknik Digital Imaging - Diny Anggriani Adnas; Mudrikah Nur Fauzi (Journal of Information System and Technology (JOINT), 2022)
Cats are mammals that have a cute and adorable body. Cats are also tame animals, so they are often used as pets. Even in Egypt, the cat is one of the animals that is used as a symbol of the purity of the Egyptians. Besides Egypt, the Muslim community also considers cats to be sacred animals. In the hadith the Prophet also mentions one of the animals, namely a cat. This is what causes the author to be interested in using cats as a source of ideas for designing and developing illustrated story books. The method used in this design is the design thinking method with five stages, namely empathize, define, ideate, prototype and test. In the process of designing the illustration book, the illustrations are drawn manually on paper, then the tracing and colouring process is carried out using Adobe Photoshop CS6 software. It is also interspersed with digital imaging techniques in the design process. The result of this design is in the form of an illustrated story book that makes it easier for readers, especially children, to understand the story of the Prophet Muhammad SAW about the specialty of cats.